(−)-Methyl-Oleocanthal, a New Oleocanthal Metabolite Reduces LPS-Induced Inflammatory and Oxidative Response: Molecular Signaling Pathways and Histones Epigenetic Modulation - Tatiana Montoya; Catalina Alarcón-; María Luisa Castejón; Juan Ortega-Vidal; Joaquín Altarejos; Marina Sánchez-Hidalgo (MDPI AG, 2021)
The antioxidant and anti-inflammatory responses of (−)-methyl-oleocanthal (met-OLE), a new metabolite of the extra virgin olive oil (EVOO) phenolic oleocanthal (OLE), were explored in lipopolysaccharide (LPS)-induced murine peritoneal macrophages. Possible signaling pathways and epigenetic modulation of histones were studied. Met-OLE inhibited LPS-induced intracellular reactive oxygen species (ROS) and nitrite (NO) production and decreased the overexpression of the pro-inflammatory enzymes COX-2, mPGES-1 and iNOS in murine macrophages. In addition, met-OLE was able to significantly decrease the activation of p38, JNK, and ERK mitogen-activated protein kinases (MAPKs) and blocked canonical and non-canonical inflammasome signaling pathways. On the contrary, met-OLE upregulated haem oxigenase 1 (HO-1) and nuclear factor (erythroid-derived 2)-like 2 (Nrf-2) expression in treated cells. Finally, met-OLE pretreated spleen cells counteracted LPS induction, preventing H3K18 acetylation or H3K9 and H3K27 demethylation. Overall, these results provide novel mechanistic insights into the beneficial effects of met-OLE regarding the regulation of the immune-inflammatory response through epigenetic changes in histone markers. This revealing evidence suggests that the methylated metabolite of OLE may contribute significantly to the beneficial effects that are associated with the secoiridoid-related compound and the usual consumption of EVOO.